Mind the context gap: a critical review of engagement within the public sector and an agenda for future research. Issue 1 (2nd January 2020) - Fletcher, Luke; Bailey, Catherine; Alfes, Kerstin; Madden, Adrian
Abstract: In this review paper, we critically examine the evidence base relating to engagement within the public sector given a wide range of public services have faced acute human resource challenges over recent years. Our review of 188 empirical studies reveals that much of the evidence focuses attention on individual and job level factors, such that specific public sector contextual contingencies have rarely been considered. Through identifying significant 'context gaps', we present a future research agenda addressing the following key areas: i) clarifying the relationship between engagement and public service motivation, ii) further contextualizing general engagement models, iii) exploring cultural, socio-political, and institutional factors in more depth, iv) encouraging a more critical perspective on engagement, v) understanding the variation in the experience of engagement across different public services/delivery models, and vi) connecting more strongly with practical concerns and initiatives within public organizations. In presenting this agenda, we highlight how engagement and HRM scholars can more strongly embed their research within a sectoral context.